Impact of Eye-Leg Coordination in Volitional Stepping on a Moving Target Compared Between Young and Middle-Aged Adults (International Journal of Physiotherapy, 2025)
Background: Coordinating vision with movement is essential for precise foot placement during volitional stepping, especially in dynamic conditions. Visual feedback enables preplanning and real-time corrections to ensure accuracy. This study aimed to determine the effect of age on eye-leg coordination by comparing stepping performance between younger and middle-aged adults.Methods: This observational study included 60 healthy participants: 30 young adults (17 females, 13 males) and 30 middle-aged adults (15 females, 15 males). A 157-inch tape line guided a lightweight ball synchronized with metronome beats at 35, 45, and 55 beats per minute (BPM). Participants performed voluntary stepping onto a moving ball with both legs. Key spatiotemporal parameters assessed were reaction time, response time, movement time, foot placement error, and missed steps.Results: Movement time significantly decreased with increasing tempo. For both legs, movement time at 35 BPM was significantly longer than at 55 BPM (right leg: p = .004; left leg: p = .012). Across all tempos, middle-aged adults demonstrated longer movement times than younger adults (35 BPM: right p = 0.003, left p < 0.001; 45 BPM: right p < 0.001, left p = 0.003; 55 BPM: right p < 0.001, left p < 0.001). Middle-aged adults also showed greater foot placement errors. They missed steps increased with tempo in both groups, with greater inaccuracies, particularly in the nondominant leg of middle-aged adults.Conclusion: Eye-leg coordination declines with age, affecting stepping accuracy and speed. Findings highlight the need for targeted balance training and fall prevention strategies to maintain mobility and reduce the risk of falls in aging populations.